NATURAL HISTORY AND MERISTICS OF AN ALLOPATRIC POPULATION OF RED CORNSNAKES, PANTHEROPHIS GUTTATUS (LINNAEUS, 1766) IN CENTRAL KENTUCKY, USA - Bird, William M.; Peak, Philip; Baxley, Danna L. (Journal of North American Herpetology, 2015)
Life history, morphological variation, and basic biology of Pantherophis guttatus (Linnaeus, 1766), the Red Cornsnake, are not well known, particularly for the allopatric populations in Kentucky. To address some of the information gaps for this species, we report field observations, including activity patterns, reproduction, and meristics of P. guttatus in Kentucky. In 2003 and 2004 we conducted field surveys using drift fences, artificial cover, manual searching, and driving on roads and captured 101 P. guttatus in Edmonson and Hart counties, Kentucky. We found that artificial cover was the best method of detection with 77% of snakes captured using this method. Numbers of encounters peaked in April-May and August-September suggesting bimodal activity patterns similar to other colubrid snakes. Males had signifi cantly higher subcaudal scale counts than females while females had significantly higher ventral scale counts than males. We detected more individuals in 2003 than in 2004, most likely influenced by severe drought conditions in Kentucky during 2004. Size-class distribution of snakes was skewed towards large individuals (> 70 cm SVL). The absence of individuals in juvenile size classes (30 cm -70 cm) may be an artifact of lower detection probabilities for smaller size classes, different habitat use by juveniles, or may indicate low recruitment.